2021
DOI: 10.1088/1755-1315/677/2/022107
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient value and antioxidant activity of malt wheat sprouts

Abstract: Currently, one of the main directions of development of the food and processing industry is to expand the range of fortified food products using secondary raw materials of grain crops. Secondary raw materials of grain crops include by-products of malt production - malt wheat sprouts, which can be used as a food fortifier. The article presents the results of the research on the micronutrient composition of malt wheat sprouts (12 batches) obtained during the germination of wheat grains of the sort “Moskovskaya-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Our results showed that the biggest bioaccessibility value for vitamin B6 was 52.94% for the BSG4 sample, probably because wheat sprouts have greater amounts of B group vitamins than barley sprouts. Moreover, wheat sprouts contain pantothenic acid, which was not identified in barley sprouts [62].…”
Section: Discussionmentioning
confidence: 89%
“…Our results showed that the biggest bioaccessibility value for vitamin B6 was 52.94% for the BSG4 sample, probably because wheat sprouts have greater amounts of B group vitamins than barley sprouts. Moreover, wheat sprouts contain pantothenic acid, which was not identified in barley sprouts [62].…”
Section: Discussionmentioning
confidence: 89%
“…The need to adhere to a certain diet leads to a decrease in the intake of basic food, biologically active substances, including vitamins and minerals from food, a violation of their assimilation and metabolism. Therefore, the need for these substances of consumers with metabolic disorders not only does not decrease, but on the contrary, increases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%